Code-Switching In English Language Teaching-Learning Process - Muthiasari, Gida; Lio, Asrun; Tambunan, Tambunan (Journal of Language Education and Educational Technology (JLEET), 2017)
It is quite ordinary for bilingual speakers to use two or more languages, in the same conversation, without any apparent effort. This phenomenon, known as code-switching, has become a major focus of attention in linguistics. The objectives of this research are to describe form, type and factors of code-switching occur. The data were taken from English Language Study Program second and fourth-semester students at IAIN Kendari. Data were collected using primary sources, observation, and interview through a questionnaire. The Ethnographic analysis table was applied to define form and type of code-switching. In addition, a questionnaire was used to reveal the factors of code-switching. The findings showed that the form of code-switching used by the students was English-Indonesian. Moreover, the type of code-switching mostly used by the students is intra-sentential code-switching. Factors of code-switching have been sorted out considering theories presented by sociolinguistics expert that all of these factors are important in second language acquisition for students in classroom setting. The findings can help to clarify that code-switching can be seen as a supporting element in the communication of information and in social interaction. Therefore, code-switching improves communication and is used as a tool for conveying meaning.